(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Reading competence is a crucial component of English as a Foreign Language (EFL) learning at the primary education level. For young learners, reading development requires not only linguistic input but also meaningful, motivating, and culturally rich materials. This article examines the role of folktales in developing reading skills among 5th grade EFL learners. Drawing on theories of narrative-based learning, extensive reading, and communicative language teaching, the paper highlights how folktales contribute to reading comprehension, vocabulary development, and learner engagement. The analysis demonstrates that folktales, due to their predictable structure, repetitive language, and cultural relevance, create supportive conditions for effective reading instruction in primary EFL classrooms. The article concludes with pedagogical implications for integrating folktales into reading curricula to enhance both linguistic and cognitive development.